Effect of subjective effort on stroke timing in breaststroke swimming - Ohba, M.; Sato, S.; Shimoyama, Y.; Sato, D. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: Competitive swimmers require the capacity to change swimming speed to control their output. Nevertheless, controlling their own motion is difficult for athletes. They attempt to control their own motion depending on subjective sensations. This study examined the relation between stroke motion and subjective efforts during breaststroke swimming (BR) in comparison with front crawl swimming (FC). METHODS: In this study, 22 well-trained college swimmers participated after giving their consent. Eight 25-m swim trials were conducted, consisting of two styles (FC and BR) and four levels of subjective effort. The levels were four steps from 70-100% effort with the same clearance for one fs maximal effort. The swimming velocity (SV, m/s) was calculated with each swimming record. The stroke rates (SR, strokes/min) were calculated from videotaped data of the swimmers. A second camcorder was placed underwater to record the swimmers for at least one complete stroke cycle, supporting analyses of the stroke phases (divided into three phases). Data were presented as mean ± standard deviation (SD). A stroke × grading level (2 × 4) repeated measures ANOVA was used to assess the significance of changes with grading level between strokes. Tukey fs post hoc test was used. RESULTS and DISCUSSION: A significant positive correlation was found between subjective effort and SV. The regression equations of FC and BR were, respectively, Y=0.67X+0.335 (r=0.99, p<0.01) and Y=0.42 X+0.587 (r=0.97, p<0.01). Increasing and decreasing the swimming velocity depends remarkably upon SR, not only for FC but also for BR. However, a significant interaction (p = 0.011) was found for SV. No significant interaction (p = 0.821) was found for SR. Both strokes have the same ratio of SR increase as stepping up the subjective effort, but not the same ratio of SV increase. Results show that the degree of SV increase by SR increase in BR is less than in FC, which might be attributed to technical characteristics: the difference between the alternate arm stroke in FC and in the simultaneous arm stroke in BR. CONCLUSION: In conclusion, increasing and decreasing the swimming velocity depends remarkably upon SR, not only in FC but also in BR. However, the degree of the SV increase by the SR increase in BR is expected to be less than in FC. These results suggest that changing SV with subjective effort in race and training is available as a difference of style.